2019
DOI: 10.1016/j.nicl.2019.102025
|View full text |Cite
|
Sign up to set email alerts
|

Tau PET and multimodal brain imaging in patients at risk for chronic traumatic encephalopathy

Abstract: HighlightsElevated tau PET signal was seen in a subset of patients at risk for CTE.Highest tracer retention was found in patients with positive amyloid PET.Tau PET, FDG and MRI showed converging abnormalities in frontotemporal regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 73 publications
7
70
0
Order By: Relevance
“…This pattern was clearly shown in this individual using a new tau tracer 18 F-MK6240. This pattern of tau tracer distribution has been reported in group-level analyses of symptomatic retired NFL players imaged with Flortaucipir ( 16 , 17 ) and a case report of a retired NFL player with CTE confirmed by neuropathological examination ( 18 ). However, quantitative tau results were within the range of control participants in the case–control studies, and limited antemortem–postmortem correlation was observed in the case study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This pattern was clearly shown in this individual using a new tau tracer 18 F-MK6240. This pattern of tau tracer distribution has been reported in group-level analyses of symptomatic retired NFL players imaged with Flortaucipir ( 16 , 17 ) and a case report of a retired NFL player with CTE confirmed by neuropathological examination ( 18 ). However, quantitative tau results were within the range of control participants in the case–control studies, and limited antemortem–postmortem correlation was observed in the case study.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, a study using the tau tracer 18 F-AV1451 (Flortaucipir) identified higher tracer retention in bilateral superior frontal, bilateral medial temporal, and left parietal regions in retired National Football League (NFL) players relative to controls, in grouplevel analyses (16). This frontotemporal pattern has also been reported in another group-level analysis of retired NFL players (17), but neither study had neuropathological confirmation of CTE. In both studies, the pattern was not a consistent feature at an individual level and the quantitative results overlapped with the control range.…”
Section: Introductionmentioning
confidence: 93%
“…For CTE, there is a modest correlation between Tauvid PET results and postmortem pathology [ 53 ]. Various studies have shown some potential of Tauvid for CTE but it still has its limitations [ 53 , 54 , 55 , 56 ]. Further studies with second-generation tracers might elucidate the use of tau PET imaging in CTE and other tau-related neurodegenerative diseases.…”
Section: Perspectivementioning
confidence: 99%
“…Younger people may experience more behavioural and/or mood symptoms with older persons exhibiting cognitive and motor impairment similar to dementia (Davis et al, 2015;Huber et al, 2016;Bailes et al, 2015;Bieniek et al, 2015;Stern et al, 2013). The causes of CTE vary by study with some stating that a single blunt force episode may be sufficient (Omalu et al, 2011) with others stating that CTE develops following repetitive concussive or sub-concussive events (Armstrong et al, 2016;Omalu et al, 2010;Edwards et al, 2017;Huber et al, 2016;Lesman-Segeva et al, 2019;McKee, Abdolmohammadi et al, 2018;Stern et al, 2011;Tsai, 2020;VanItallie, 2019) or both (Bailes et al, 2019). Limited prevalence data suggest that CTE has been observed in 9% of autopsy cases with a history sport participation versus 3% of those with no history of participation in sport (Bieniek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%